2021
DOI: 10.22452/mjcs.sp2021no2.8
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Discrete Wavelet Transform and Texture Analysis Methods for Feature Extraction and Classification of Breast Dynamic Thermogram Sequences

Abstract: Breast cancer is a common cancer that hits women causing thousands of casualties every year. A cancerous tumor causes an increase of temperature near the region of the tumor. The heat generated by the temperature transferred to the skin surface. The temperature in the tumor area is warmer than in the healthy area. Detecting breast cancer in early stages can save women’s lives and lower the burden on the cost. Thermography is an imaging technique used for breast cancer detection. A dynamic thermography techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Thermograms have played a significant role in diagnostic imaging studies. They serve as a source for developing image processing activities, which include segmentation tasks for separating the regions under study, as presented in [ [5] , [6] , [7] , [8] , [9] , [10] ] and identification of descriptive features and classification, as published [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Although most studies reported before 2014 were conducted without public access images sets that prevented reproducibility and comparison of results, it was until 2014 that the first public database of breast thermographic images was presented.…”
Section: Introductionmentioning
confidence: 99%
“…Thermograms have played a significant role in diagnostic imaging studies. They serve as a source for developing image processing activities, which include segmentation tasks for separating the regions under study, as presented in [ [5] , [6] , [7] , [8] , [9] , [10] ] and identification of descriptive features and classification, as published [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Although most studies reported before 2014 were conducted without public access images sets that prevented reproducibility and comparison of results, it was until 2014 that the first public database of breast thermographic images was presented.…”
Section: Introductionmentioning
confidence: 99%